Explaining Health Across the Sciences - Sholl, Jonathan; Rattan, Suresh I.S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This edited volume aims to better understand the multifaceted phenomenon we call health. Going beyond simple views of health as the absence of disease or as complete well-being, this book unites scientists and philosophers. The contributions clarify the links between health and adaptation, robustness, resilience, or dynamic homeostasis, and discuss how to achieve health and healthy aging through practices such as hormesis. The book is divided into three parts and a conclusion: the first part explains health from within specific disciplines, the second part explores health from the perspective of a bodily part, system, function, or even the environment in which organisms live, and the final part looks at more clinical or practical perspectives. It thereby gathers, across 30 chapters, diverse perspectives from the broad fields of evolutionary and systems biology, immunology, and biogerontology, more specific areas such as odontology, cardiology, neurology, and public health, as well as philosophical reflections on mental health, sexuality, authenticity and medical theories. The overarching aim is to inform, inspire and encourage intellectuals from various disciplines to assess whether explanations in these disparate fields and across biological levels can be sufficiently systematized and unified to clarify the complexity of health. It will be particularly useful for medical graduates, philosophy graduates and research professionals in the life sciences and general medicine, as well as for upper-level graduate philosophy of science students.
Keywords: Medicine; Medicine$1 (BPhilosophy.s; Philosophy and science; Biomedicine, general; Philosophy of Medicine; Medicine/Public Health, general; Philosophy of Science